mPSQed: A Software for the Design of Multiplex Pyrosequencing Assays - Dabrowski, Piotr Wojtek (Public Library of Science, 2012)
Molecular-based diagnostic assays are the gold standard for infectious diseases today, since they allow a rapid and sensitive identification and typing of various pathogens. While PCR can be designed to be specific for a certain pathogen, a subsequent sequence analysis is frequently required for confirmation or typing. The design of appropriate PCR-based assays is a complex task, especially when conserved discriminating polymorphisms are rare or if the number of types which need to be differentiated is high. One extremely useful but underused method for this purpose is the multiplex pyrosequencing technique. Unfortunately there is no software available to aid researchers in designing multiplex pyrosequencing assays. Here, we present mPSQed (Multiplex PyroSeQuencing EDitor), a program targeted at closing this gap. We also present the design of an exemplarily theoretical assay for the differentiation of human adenovirus types A–F using two pyrosequencing primers on two distinct PCR products, designed quickly and easily using our software.